Smart physics II: Electricity and magnetism - Y S Vidya...[et.al]; VIDYA (Y S); MANJUNATHA (H C); SEENAPPA (L); SRIDHAR (K N) (Bangalore Sunstar Publisher, 2022)
Text book is written in accordance with the NEP syllabus prescribed by the Bangalore north, Bangalore South University for II sem BSc course. This book includes a comprehensive coverage of theoretical concepts with large number of graded numerical problems to understand the subject thoroughly. The flow of content and concept questions are presented in such a manner that an average student also score good marks in the university examination.
Keywords: Electric Charge and Field; Electrostatic Potential; Network Theorems; Conductors in Electrostatic Field; DC Currents; Magnetism; NEP BSc II Semester